THE IMPACT SOCIAL MEDIA MARKETING, SOCIAL INTERACTIVITY AND PERCEIVED QUALITY OF BRAND LOYALTY ON IPHONE USERS - Simatupang, Michael Sabato; Purba, Hedry (Jurnal Riset Manajemen dan Akuntansi, 2023)
Brand loyalty plays a crucial role in social media services for consumers. Marketing activities through social media can predict and focus on consumer values in brand selection and sharing information with other consumers through social media. Therefore, the purpose of this study is to investigate the impacts of Social Media Marketing, Social Interactivity, and Perceived Quality on Brand Loyalty among iPhone users. The research employed a survey method, and a set of questionnaires were administered to 117 iPhone users located in a specific area via Google Forms. Structural Equation Modelling (SEM) and SmartPLS 4 were utilized to analyze the collected data. The findings demonstrated that Social Media Marketing has a significant simultaneous effect on brand loyalty among iPhone users, although its partial effects were insignificant. Effective Social Media Marketing can enhance iPhone users' loyalty to the brand as they actively engage in marketing campaigns on social media. Social Interactivity also has a significant effect on brand loyalty among iPhone users. Social interactions between users and the brand on social media influence user engagement, relationship, and experience with the brand, which in turn affects iPhone users' loyalty. Perceived Quality also plays a crucial role in influencing brand loyalty among iPhone users. iPhone users who perceive the product as high-quality tend to be more loyal to the brand. There are interrelated relationships between Social Media Marketing, Social Interactivity, and Perceived Quality in shaping brand loyalty among iPhone users. Therefore, Marketers and brand managers should focus on developing effective social media strategies, good user interactions, and product quality enhancement to improve user loyalty to the iPhone brand.